Determination of Polycyclic Aromatic Hydrocarbon (PAHs) in the Tigris River through Passing Baghdad Province - A. Al-Azawii, Luma H.; R. Nashaat, Muhnned; N.Al-Azzawi, Muhammad (Iraqi Journal of Science, 2023)
Tigris River receives many pollutants while passing through Baghdad province due to increasing of population, discharge of untreated industrials, agricultural wastes on the river. The present study was conducted from January 2013 to December 2013 on the Tigris River starting from Al-Muthana Bridge to Al-Zaufurania city before it's jointed with Diyalla Tributaries. Six stations were chosen on the Tigris River along Baghdad city. The study was included measuring the bimonthly concentrations and distributions of polycyclic aromatic hydrocarbons (PAHs) in the samples of surface water. The sixteen polycyclic aromatic hydrocarbons (PAHs) listed by USEPA as priority pollutants (Naphthalene, Acenaphthalene, Acenaphthene, Fluorene, Phenanthrene, Anthracene, Flouranthene, Pyrene, Benzo(a)anthracene, Chrysene, Benzo(b)flouranthene, Benzo(k)fluoranthene, Benzo(a)pyrene, Pyrene, Dibenzo(a,h)anthracene, benzo(g,h,i)perylene and Inden(1,2,3-cd)pyrene) were detected. The highest value of total PAHs was 0.279 ppm recorded during August 2013 whereas the lowest value was 0.007 ppm during October 2013 at Al-Durah power plant discharge sit. The lowest value of (0.0002) ppm was recorded for Fluorene and Fluoranthene, while the highest value of (0.2) ppm for Naphthalene at Al-Durah power plant sit.